2021
DOI: 10.3390/s21041540
|View full text |Cite
|
Sign up to set email alerts
|

Using Secure Multi-Party Computation to Protect Privacy on a Permissioned Blockchain

Abstract: The development of information technology has brought great convenience to our lives, but at the same time, the unfairness and privacy issues brought about by traditional centralized systems cannot be ignored. Blockchain is a peer-to-peer and decentralized ledger technology that has the characteristics of transparency, consistency, traceability and fairness, but it reveals private information in some scenarios. Secure multi-party computation (MPC) guarantees enhanced privacy and correctness, so many researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 33 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Privacy preservation is ensured by verifiable secret sharing, and secure multiparty computation is used to enhance security, efficiency, and fairness. Zhou et al [21] explored the privacy protection features of secure multiparty computation in the permissioned blockchain. This work integrated a secure MPC protocol in Hyperledger Fabric.…”
Section: Related Workmentioning
confidence: 99%
“…Privacy preservation is ensured by verifiable secret sharing, and secure multiparty computation is used to enhance security, efficiency, and fairness. Zhou et al [21] explored the privacy protection features of secure multiparty computation in the permissioned blockchain. This work integrated a secure MPC protocol in Hyperledger Fabric.…”
Section: Related Workmentioning
confidence: 99%
“…, y n . As soon as the computation completes, each party P i is required to acquire its own corresponding output y 1 without obtaining any other kind of information [63].…”
Section: Multi-party Computation For Achieving Blockchain Privacymentioning
confidence: 99%
“…Cryptographic protocols such as Multi-Party Computation (MPC) can enhance privacy and when combined with blockchain and smart contracts, it can help address the security, trust, and verifiability issues in distributed analytics [138]. Current research in this field has shown the feasibility of performing distributed privacy-preserving analysis on blockchain [51,139]. Researchers can further investigate and develop new approaches for genomic applications.…”
Section: Future Directionsmentioning
confidence: 99%